2007
DOI: 10.5713/ajas.2007.1865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Metabolizable Energy and Lysine on Carcass Characteristics and Meat Quality in Arbor Acres Broilers

Abstract: An experiment was performed to evaluate the effects of dietary metabolizable energy (ME) and lysine on carcass characteristics and meat quality in Arbor Acres (AA) broilers from 1 to 56 days of age. A total of 2,970 1-d-old male broiler chicks were randomly allocated to nine dietary treatments (three ME levels in combination with three lysine levels), and dietary ME and lysine concentrations were formulated by varying corn, soybean meal, tallow, and L-lysine sulfate concentrations. Live body weight (BW), carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 65 publications
4
27
1
2
Order By: Relevance
“…This finding, while being consistent with that of Nguyen and Bunchasak (2005), on the Thailand Betong native chicken and Magala et al (2012) on Uganda local chickens, was different from the observations of Niu et al (2009), Alabi et al (2013 on commercial broilers and Venda chicks respectively. This may be due to breed differences which have different gene encoding key regulatory factors such as hormones, enzymes and metabolic pathways (Richards and Proszkowiec-Weglarz, 2007;Tang et al, 2007). Emmans and Fisher (1986) and Emmans (1989) indicated that chickens grow based on their genetic potential; thus, they attempt to eat as much of a given feed as would be required to satisfy their growth needs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, while being consistent with that of Nguyen and Bunchasak (2005), on the Thailand Betong native chicken and Magala et al (2012) on Uganda local chickens, was different from the observations of Niu et al (2009), Alabi et al (2013 on commercial broilers and Venda chicks respectively. This may be due to breed differences which have different gene encoding key regulatory factors such as hormones, enzymes and metabolic pathways (Richards and Proszkowiec-Weglarz, 2007;Tang et al, 2007). Emmans and Fisher (1986) and Emmans (1989) indicated that chickens grow based on their genetic potential; thus, they attempt to eat as much of a given feed as would be required to satisfy their growth needs.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 10 days of the ELCP diet reduced the CSA compared with the control diet. According to Tang et al (2007), a highenergy diet decreased the SFV of chicken breast muscle. The lowest mean CSA was found in the LCP group, but the SFV of the LCP group was not as low as that of the ELCP group.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in energy intake could explain the SFV disparities. According to Tang et al (2007), a highenergy diet decreased the SFV of chicken breast muscle. The dietary energy intake should have been higher in the ELCP group than the other two groups because the FI of the ELCP group was higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, the values obtained from the Venda chickens are lower than those for broiler chickens as proposed by NRC (1994). Differences in dietary energy levels for optimal feed intake between Venda and broiler chickens may be related to differences in energy requirements (NRC, 1994;Mbajiorgu 2010;Mbajiorgu et al, 2011). Tang et al (2007 reported that differences in responses to dietary energy levels might be attributed to breed differences.…”
Section: Resultsmentioning
confidence: 99%